Le Livre des Morts et le travail de rédaction des scribes-copistes : le cas du papyrus Louvre E 11078 - Silvia Einaudi (Les Cahiers de l'École du Louvre)
The ancient Egyptian Book of the Dead is a collection of magic-religious formulas, whose aim was to aid the deceased on his way to a happy life in the hereafter. Beginning mainly in the New Empire, this funerary composition is attested to on the shrouds, coffins, papyri, the walls of the tombs, funerary statuettes (shabtis), amulets and mummy bandages. The Pasenedjemibnakht papyrus (Louvre E 11078) contains a Book of the Dead that has been preserved in its entirety, give or take a few lacunae. The roll (19.44 metres) contains 153 formulas. It comes from the town of Akhmīm and most likely date from the second half of the fourth century BC (end of the Late period – beginning of the Ptolemaic period).